2003
DOI: 10.1186/1471-2350-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of common variants at the Apo E, Apo AI, Apo CIII, Apo B, lipoprotein lipase (LPL) and hepatic lipase (LIPC) genes and coronary artery disease (CAD): variation in LIPC gene associates with clinical outcomes in patients with established CAD

Abstract: BackgroundCurrent evidence demonstrates that positive family history and several alterations in lipid metabolism are all important risk factors for coronary artery disease (CAD). All lipid abnormalities themselves have genetic determinants. Thus, objective of this study was to determine whether 6 genetic variants potentially related to altered lipid metabolism were associated with CAD and with lipid abnormalities in an Italian population. These genetic variables were: apolipoprotein E (Apo E), Apo AI, Apo CIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 31 publications
4
44
1
1
Order By: Relevance
“…Interestingly total plasma cholesterol did not discriminate between cases and controls as in other European countries [20]. Multiple regression analysis confirmed the independent predictive role for all of the above mentioned lipid parameters [21,22].…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly total plasma cholesterol did not discriminate between cases and controls as in other European countries [20]. Multiple regression analysis confirmed the independent predictive role for all of the above mentioned lipid parameters [21,22].…”
Section: Discussionsupporting
confidence: 51%
“…However, although the frequency of the S allele was 33% in Turks, it was not associated with HDL-C levels or hepatic lipase activity. The frequency of T224T was similar in Finnish cases and controls ( 11 ), but was signifi cantly lower in Italian coronary heart disease patients than controls (36% vs. 53%) ( 53 ). This variant was not associated with lipid parameters in Turks.…”
Section: Discussionmentioning
confidence: 94%
“…7,[21][22][23][24] Furthermore, other genes such as the ApoE, ApoA1, ApoB, hepatic lipase and PPAR genes have been investigated for their association with lipid levels and/or cardiovascular disease outcomes. 4,10,[25][26][27] Since weight gain and BMI are significantly correlated with serum triglycerides and cholesterol levels, it is possible that genetic variants which may influence the extent of weight gain during treatment with antipsychotics, such as the polymorphisms in the 5-HT2C receptor (À759 T/C), 28,29 polymorphisms of the leptin gene, 28,30 and polymorphisms in the a2A receptor (À1291 C/G) 31 may also be related to deferential drug  gene effects on serum lipids. In this initial study, we could only investigate a few polymorphisms which previous studies suggested may have significant effects on plasma or serum triglycerides or cholesterol; we also chose SNPs with a minor allele frequency of at least 10% in some prior studies.…”
Section: Discussionmentioning
confidence: 99%